Enterprise risk management practices and firm performance, the mediating role of competitive advantage and the moderating role of financial literacy - Songling Yang; Muhammad Ishtiaq; Muhammad Anwar (Journal of Risk and Financial Management, 2018)
In the current turbulent market, firms spend lots of tangible and intangible resources to gain competitive advantage and superior performance. Prior studies have discussed several determinants of competitive advantage and performance, particularly in developed economies, whereas small- and medium-sized enterprises (SMEs) in emerging economies have received minor attention. This study examines the mediating role of competitive advantage between enterprise risk management practices and SME performance and the moderating role of financial literacy between enterprise risk management practices and competitive advantage. A structured questionnaire is used to collect data from 304 SMEs operating in the emerging market of Pakistan. The hypotheses of the proposed study are tested through Structural Equation Modeling (SEM) in Analysis of a Moment Structures (AMOS). The results indicate that enterprise risk management practices significantly influence competitive advantage and SME performance. Competitive advantage partially mediates the relationship between enterprise risk management practices and SME performance. Additionally, financial literacy significantly moderates the relationship between enterprise risk management practices and competitive advantage. Firms are advised to implement formal enterprise risk management practices to gain competitive advantage and superior performance. Top managers need to have enough financial education that they will be able to perform risk management practices in an efficient way to gain a competitive position in the market. Implications for practices have been discussed in detail.
Keywords: 330; enterprise risk management practices; competitive advantage; financial literacy; SMEs performance